Halal sebagai Label atau Nilai (Telaah Filosofis Maqāṣid al-Syarī‘ah dalam Pengembangan Sistem Ekonomi Islam) - Fikri, Miftahul; Lutfi, Ahmad; Iska, Syukri (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2026)
This article examines the phenomenon of the reduction of maqāṣid al-syarī‘ah in contemporary halal practices, where halal is often understood as a legal-formal label rather than a normative value serving as the systemic foundation of Islamic economics. Using a Systematic Literature Review (SLR) of 20 primary articles and 10 additional references, this study highlights the tension between the normative ideals of maqāṣid and practical implementation in halal industries, SMEs, and Islamic banking. Findings reveal that halal certification is often treated as an administrative tool or marketing strategy, while principles of welfare, quality, sustainability, and justice are insufficiently realized. The study emphasizes the urgency of restoring maqāṣid al-syarī‘ah as a comprehensive normative foundation, ensuring halal functions as a guiding value within the Islamic economic system. This research contributes philosophically and practically, providing guidance for the development of an integrative, holistic, and sustainable Islamic economy.